A Power System Analysis for Large Scale Solar Photovoltaic System using PVSyst and ETAP - Mohd Zamri , Nur Dini Shahirah; Abdullah, Mohd Noor (Evolution in Electrical and Electronic Engineering, 2022)
Renewable energy (RE) field has been listed as one of the alternative energy solutions for the global energy transition to zero-carbon energy generation by 2050. This is because Malaysia has benefited from the exploration of the country’s potential for Large Scale Solar Photovoltaic (LSS PV) installations. However, LSS often faced technical challenges in the LSS PV to the power grid integration. The technical challenges can be classified as voltage instability, reactive power regulation, and short circuit power deviations. In this project, the two methods are used which are PVSyst and ETAP software. The aims of this project are to design a Grid Connected Photovoltaic system using PVSyst simulation and analyze the power system network for the transmission connected LSS plant to the grid system using ETAP software and investigate the performance of grid connection to be able to comply with Grid Code requirements. The PVSyst simulation result showed that the system is able to produce a 41 to 42 MW capacity of AC rating using three different PV modules. By using the output rating from the PVSyst, the PV system is then integrated into Bus 7 where the findings of this project found that the deviations in bus voltages were minimal and the network was able to operate within the specified limits.